Tumour control and Quality of Life in children with rhabdomyosarcoma treated with pencil beam scanning proton therapy. Issue 1 (July 2016) - Leiser, Dominic; Calaminus, Gabriele; Malyapa, Robert; Bojaxhiu, Beat; Albertini, Francesca; Kliebsch, Ulrike; Mikroutsikos, Lorentzos; Morach, Petra; Bolsi, Alessandra; Walser, Marc; Timmermann, Beate; Lomax, Tony; et al.
Abstract: Purpose: To assess clinical outcomes in children with rhabdomyosarcoma (RMS) treated with pencil beam scanning (PBS) proton therapy (PT). Methods and materials: Eighty-three RMS (embryonal, n = 74; 89%) patients treated between January 2000 and December 2014 were included. The median age was 4.5 years (range, 0.8–15.5). All patients received systemic chemotherapy according to prospective protocols. Patients had low-, intermediate-, and high-risk disease in 24%, 63%, and 13% of cases, respectively. The median total dose delivered was 54 Gy(RBE) (range, 41.4–64.8). Results: After a median follow-up time of 55.5 months (range, 0.9–126.3), local failure occurred in 16 patients. The 5-year local-control survival rate was 78.5% [95% confidence interval (CI), 69.5–88.5%]. Significant predictors for local failure were group/stage, tumour location, and size. Fourteen patients (16%) died, all from tumour progression. The 5-year overall survival was 80.6% (95%CI, 71.8–90.0%). The 5-year incidence of grade 3 non-ocular late toxicity was 3.6% (95%CI, 1–12%). No grade 4–5 late toxicities were observed. One radiation-induced malignancy was observed (1.2%). The Quality of Life (QoL) scores increased significantly after PT compared to baseline values. Conclusions: PBS PT led to excellent outcome in children with RMS. Late non-ocular toxicity was minimal and QoL good.